Progression risk stratification with six-minute walk gait speed trajectory in multiple sclerosis - Goldman, Myla D.; Chen, Shanshan; Motl, Robert; Pearsall, Rylan; Oh, Unsong; Brenton, J. Nicholas (Frontiers in Neurology, 2023)
Background: Multiple Sclerosis (MS) disease progression has notable heterogeneity among patients and over time. There is no available single method to predict the likelihood of progression, which represents a significant and unmet need in MS. Methods: MS and healthy control (HC) participants were recruited for a 2-year observational study. A latent-variable growth mixture model (GMM) was applied to cluster baseline 6-minute walk gait speed trajectories (6MWGST). MS patients within different 6MWGST clusters were identified and sub-grouped. The group membership of these MS patients was compared against 2-year confirmed-disease progression (CDP). Clinical and patient-reported outcome (PRO) measures were compared between HC and MS subgroups over two years. Results: 62 MS and 41 HC participants completed the 2-year study. Within the MS cohort, 90% classified as relapsing MS. Two distinct patterns of baseline 6MWGST emerged, with one cluster displaying a faster gait speed and a typical “U” shape, and the other showing a slower gait speed and a “flattened” 6MWGST curve. We classified MS participants in each cluster as low- and high-likelihood progressors (HLP and LLP, respectively). When compared against 2-year CDP, our 6MWGST approach had 71% accuracy and 60% positive predictive value. Compared to the LLP group, those MS participants classified as HLP (15/62, 24%), were average 3.8 years older, had longer MS disease duration, and baseline poorer performance on clinical outcomes and PROs scores. Over the subsequent 2 years, only the HLP subgroup showed a significant worsened performance on 6MW, clinical measures and PROs from baseline. Conclusion: Baseline 6MWGST was sufficient to identify MS participants with high or low likelihoods for progression over the subsequent 2 years. Findings represent the first reported single measure to predict MS disease progression with important potential applications in both clinical trials and care in MS.